CLINICAL SAFETY OF SULFAMETHOXAZOLE-TRIMETHOPRIM TREATMENT IN NILE TILAPIA (Oreochromis niloticus) - PULTZ , M. E.; ARAÚJO , K. S.; ARACATI, M. F.; OLIVEIRA, S. L.; RODRIGUES, L. F.; KLINGER, B. A. R.; CARLINO-COSTA, C.; VIEIRA, E. C.; BELO, M. A. A. (Ars Veterinaria, 2024)
The safety and tolerability of pharmaceuticals, due to the complexity of assessing adverse effects, require the conduction of multiple studies. This necessitates extensive research and clinical trials to confirm the safety and efficacy of medications. This study evaluated the clinical safety of oral Sulfamethoxazole-trimethoprim (SMZ-TMP) treatment in Nile tilapia (Oreochromis niloticus) through hematological and biochemical assessments. A total of 63 animals (±100g) were reared in 9 tanks (n=7). Following acclimation, the treatments administered were: T0 (control, not treated with SMZ-TMP); T1 and T2 (treated with 30-6 and 120-24 mg of SMZ-TMP/kg b.w., respectively). Seven animals per treatment were sampled at 4, 8, and 12 days post-treatment, with an additional recovery period where animals were fed only commercial feed until day 16 for clinical recovery evaluation. Blood samples were collected for hematological and serum biochemical analysis, as well as somatic organ analysis. The results showed that SMZ-TMP, especially at high doses, caused hematological changes such as increased erythrocyte counts and hemoglobin levels, as well as microcytosis. Treatment with SMZ-TMP/kg modulated the response of fish white blood cells by altering circulating leukocyte levels associated with lymphocyte counts. In addition, it resulted in disorders with reductions in protein and creatinine levels, associated with anorexia and mortality in fish treated with 120-24 mg of SMZ-TMP/kg of bw, demonstrating the toxic effect of overdose treatment. However, further studies should be conducted to determine the clinical safety of different therapeutic protocols involving the use of SMZ-TMP in tilapia.